To Optimization Of Chicken Feed Production Using Goal Programming Method At PT. Japfa Comfeed Indonesia Tbk. Unit Makassar - Hanin Fitria; Dwijayanti Hasti Widyaningrum; Rahmaniah Malik; Nur Ihwan Safutra; Yan Herdianzah (Journal of Industrial System Engineering and Management, 2022)
PT Japfa Comfeed Indonesia Tbk is one of the largest and most integrated agri-food companies in Indonesia. The company's main business units are the manufacture of animal feed, chicken breeding, poultry processing, and agricultural cultivation. This company will automatically continue to increase its production results both in terms of quantity and in terms of quality to be able to compete in the market so that it can expand market share and offer products at affordable costs for consumers. At present, business progress is strongly influenced by fluctuations and variations in consumer demand. This also has an impact on the production of chicken feed carried out by PT Japfa Comfeed Indonesia Tbk Makassar unit. With the increasing demand for chicken feed, an effort is needed so that the production process runs according to available and profitable resources. This research aims to determine the optimal amount of production to generate optimal company profits. The method used in this study is the goal programming method because it can solve problems optimally with more than one goal. The results of this research show that the product of goal programming optimization is more profitable than the companies. The results obtained from this research are the optimal number of products is 4,967,155 kg, and the minimum production cost is Rp. 1,382,685,942,075, and the sales profit is Rp. 314,569,267,925 for a period of one year.